(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
As a tool for the exchange of ideas of the Uzbek nation, the Uzbek language today performs a social function. It serves to fully ensure the communication process of representatives of this nation. The onomastic system of the Uzbek language is a linguistic phenomenon rich in enormous content, multifaceted and inextricably linked to each other. The study of onomastic units occurring in the text of literary works is one of the issues awaiting a solution for linguistics. In this regard, it is important to study the lexical-semantic and stylistic features of anthroponyms in the text of literary works. Also, the contributions of our linguists, writers, and poets to the current development of the Uzbek language are incomparable. Thanks to their great work, strict norms are established in most areas of the Uzbek language, and linguistic patterns of language units in the process of communication are described.